Carcass Quality, Production of Local Duck Meat and Edible Offals in Traditional Markets on Lombok and Sumbawa Islands - Ariana, Tirta; Bulkaini, Bulkaini; Sumadi, I.K.; Syamsuhaidi, Syamsuhaidi; Sutaryono, Yusuf; Maskur, Maskur; Kisworo, Djoko; Sukarne, Sukarne (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Carcass and meat production of local male ducks can be used as indicators to assess carcass quality. The purpose of this study was to determine the quality of carcasses, meat production and offal of male local ducks in traditional markets on the islands of Lombok and Sumbawa based on the Indonesian National Standard. The research material used 64 male local ducks aged 55-60 days with details of 36 coming from chicken slaughterhouses in Mataram City, 12 ducks from chicken slaughterhouses in West Lombok Regency, and 16 ducks from chicken slaughterhouses in Sumbawa Regency. Sampling of local male ducks from each sub-district was by using random sampling. The research data consisted of live weight, carcass weight, meat weight, carcass percentage, and offal percentage were analyzed using the Microsoft Excel program and SPSS version 16 software program regression correlation analysis. Data analysis showed that local male ducks slaughtered in traditional markets on the islands of Lombok and Sumbawa produced duck carcasses belonging to quality I as much as 51.16 ± 10.68% of the total sample, quality II as much as 37.71 ± 15.28% and quality III of 17.13 ± 6.85%. Pure local male duck meat products circulating in traditional markets on the islands of Lombok and Sumbawa are 43.96% and 44.82% respectively. Conclusion: Carcass quality and meat production of local male ducks in the traditional markets of the islands of Lombok and Sumbawa have met the Indonesian National Standard, namely live weight of 1,290 g, carcass percentage of 60.33%, and pure meat production of 44.25%.